APPLICATION OF CHATGPT IN THE ANALYSIS OF INTERNAL FORCES OCCURRING IN SIMPLE BEAMS USING LISA V.8 FEA - Efendi, Aco Wahyudi (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2024)
ChatGPT (Chat Generative Pre-trained Transformer, literally Trained Chat Generative Transformer) is an artificial intelligence chatbot in the form of a generative language model that employs transformer technology to anticipate the likelihood of the next sentence or word in a conversation or text command. The increasing use of ChatGPT in all scientific lines has a positive impact as in some previous research results. In this research, we will apply the use of ChatGPT in the field of structural engineering by analyzing a steel portal due to lateral loads which will produce the drift value that occurs by validating it using the finite element analysis program LISA V.8 FEA (license) and against manual calculations. it is hoped that this research can provide satisfactory results as in previous research in other engineering and social fields. The research looked at the results and data processing outputs, as well as the comparison of the three methodologies, which were manual analysis, ChatGPT, and the Finite Element Method. Because the value of manual computation, ChatGPT, and FEA agrees with the results 95% of the time, the results of the instant value that occurs in the three reviews above are extremely satisfying. The greatest torque obtained by calculating manually, for example, is 750,000 N, which is the same as the maximum torque obtained using ChatGPT. Furthermore, the working pressure is 500 N, which is consistent with physical pressure, chatGPT, and LISA FEA V.8 (license) results. ChatGPT (Chat Generative Pre-trained Transformer, secara harfiah berarti Trained Chat Generative Transformer) adalah sebuah chatbot kecerdasan buatan berupa model bahasa generatif yang menggunakan teknologi transformator untuk mengantisipasi kemungkinan kalimat atau kata berikutnya dalam sebuah percakapan atau perintah teks. Meningkatnya penggunaan ChatGPT di semua lini keilmuan dan memberikan dampak positif seperti pada beberapa hasil penelitian sebelumnya. Pada penelitian kali ini, kami akan mengaplikasikan penggunaan ChatGPT pada bidang teknik struktur dengan menganalisa sebuah portal baja akibat beban lateral yang akan menghasilkan nilai drift yang terjadi dengan melakukan validasi menggunakan program analisis elemen hingga LISA V.8 FEA (lisensi) dan terhadap perhitungan manual. diharapkan penelitian ini dapat memberikan hasil yang memuaskan seperti pada penelitian terdahulu pada bidang teknik dan sosial lainnya. Penelitian ini melihat hasil dan output pengolahan data, serta perbandingan dari ketiga metodologi, yaitu analisis manual, ChatGPT, dan Metode Elemen Hingga. Karena nilai perhitungan manual, ChatGPT, dan FEA setuju dengan hasil 95%, maka hasil nilai instan yang terjadi pada ketiga tinjauan di atas sangat memuaskan. Torsi terbesar yang didapatkan dengan hitung manual misalnya adalah 750.000 N, sama dengan torsi maksimum yang didapatkan dengan menggunakan ChatGPT. Selanjutnya, tekanan yang bekerja adalah 500 N, yang sesuai dengan tekanan fisik, chatGPT, dan hasil LISA FEA V.8 (lisensi).